Tensile properties and constitutive model of cost-effective multiscale hybrid fiber reinforced strain hardening cementitious composites - Hou, Jin; Bai, Jianjun; Mou, Hongmei; Xiang, Zhisuo (Frontiers in Materials, 2024)
To enhance the mechanical properties and cost-effectiveness of conventional polyvinyl alcohol fiber reinforced strain hardening cementitious composite (PVA-SHCC), a modified version called multiscale hybrid fiber reinforced SHCC (MsHySHCC) was developed. This new composite incorporates a combination of steel fiber, PVA fiber and calcium carbonate (CaCO 3 ) whisker. Uniaxial direct tensile behaviors (stress-strain relationship, tensile strength, tensile deformation capacity and tensile toughness) of designed MsHySHCCs were investigated and evaluated. The results show that the PVA fibers dominate the ductile behavior and the steel fibers and CaCO 3 whiskers effectively affect the strength of MsHySHCCs. The PVA fibers can be partially replaced by CaCO 3 whisker and steel fiber, along with an increase in tensile strength and ductility of designed composites. The findings suggest that the configuration of MsHySHCC proves to be a viable approach in simultaneously enhancing the strength and ductility of PVA-SHCC. A semi-theoretical prediction model for tensile constitutive relationship was derived.The comparison of the theoretical results with the experimental data shows that this semi-theoretical model is applicable for determining the tensile constitutive relationship of PVA-SHCCs and MsHySHCCs.